Vitamin D levels are associated with trait resilience but not depression in a general population sample. Issue 12 (13th October 2020) - Terock, Jan; Hannemann, Anke; Janowitz, Deborah; Müller, Jasmin; Völzke, Henry; Grabe, Hans J.
Abstract: Introduction: Insufficient vitamin D levels were found to be related to various psychiatric disorders and particularly depression. The functional polymorphisms rs4588 and rs7041 of the vitamin D‐binding protein (also g roup‐specific c omponent or Gc) influence vitamin D level and activity. Resilience is considered the individual predisposition to maintain psychological functioning in the face of adversities. We sought to investigate whether associations of vitamin D levels and genotypes of rs4588 and rs7041 were associated with trait resilience and symptoms of depression. Methods: Serum levels of total 25(OH)D were measured in a general population sample ( n = 1, 908) of the Study of Health in Pomerania (SHIP‐1). The Resilience Scale‐25 (RS‐25) was applied to assess trait resilience. Lifetime depressive symptoms were assessed using the CID‐S, while current depressive symptoms were measured using the Beck Depression Inventory II (BDI‐II). Study participants were genotyped for rs4588 and rs7041. Results: Participants with vitamin D insufficiency had lower adjusted mean RS‐25 scores as compared to vitamin D replete subjects ( p = .002). Linear regression analyses revealed a positive association between 25(OH)D and RS‐25 scores ( ß = 2.782, p = .002). Additional adjustment for BDI‐II scores slightly attenuated this result ( ß = 1.830 and p = .026). Symptoms of depression and the lifetime diagnosis of MDD were not significantly associated with vitamin D concentrations. rs4588 and rs7041 showed strong associations with vitamin D concentrations (both p < .001), but not RS‐25 scores. Conclusions: In contrast with previous studies, our findings do not provide evidence for a strong role of vitamin D in the psychopathology of depression. However, considering the role of trait resilience as a common protective factor to different psychiatric disorders, our results support the concept of low vitamin D as a general risk factor to stress‐related psychopathologies. Abstract : We found that resilience, but not depression, was strongly associated with vitamin D levels in 1, 908 subjects from the general population. The association with resilience remained stable after adjustment for depressive symptoms. Functional polymorphisms of the vitamin D‐binding protein gene (rs4588 and rs7041) were highly associated with vitamin D levels, but neither depression nor resilience.